Javanese Islamic architecture: adoption and adaptation of Javanese and Hindu-Buddhist cultures in Indonesia - Noor Cholis Idham (Journal of Architecture and Urbanism, 2021)
Javanese Islamic architecture appears to be highly influenced by previous cultures, even though Islam has brought a new civilisation since the 13th century in Indonesia. The classical mosques and houses seem to follow Javanese and Hindu-Buddhist principles in their buildings, elements and spatial arrangements. This paper examines how the Javanese adapted their architecture to meet Islamic values while preserving their previous traditions. The concept of architectural synchronisation in Javanese architecture is examined from the traces observed in the temple dioramas, depictions of contemporary cultural products, and several traditional buildings. The adoptions and adaptations that appear in some significant objects such as old mosques and houses are traced back to previous transformation principles. Architectural harmonisation for new needs seemingly bases on religion as the most potent driving aspect. However, what is interesting is that in the case of Java, embracing a new religion does not mean forgetting existing traditions. On the other hand, the principle of acculturation has created a peaceful transition in architecture. Some evidence suggests that Javanese high culture, such as the classical grand mosque and the joglo house, succeeded in translating Javanese and Hindu-Buddhist ideas into Islamic architecture in very distinctive ways.